The vicious cycle of physical inactivity, fatigue and kinesiophobia in patients with fibromyalgia syndrome - B. Cigdem Karacay; T. Sahbaz; C. Medin Ceylan (PAGEPress Publications, 2023)
This study aims to determine the association between fatigue, kinesiophobia, disease severity, and physical inactivity by comparing fibromyalgia syndrome (FMS) patients with healthy controls. Pain and fatigue are significant barriers to the participation in functional activities. Inactivity is a result of fatigue, but exercise is the foundation of FMS treatment. This case-control study included a total of 203 participants (107 patients with FMS and 96 healthy volunteers). The fibromyalgia impact questionnaire, the fatigue severity scale, the international physical activity questionnaire, and the Tampa scale for kinesiophobia were assessed. The FMS group scored significantly higher on the fatigue severity scale and kinesiophobia than the control group (p<0.001). Significantly lower metabolic task equivalent (MET) scale values were observed in the FMS group compared to the control group (p<0.001). The severity of fatigue and kinesiophobia correlated positively with the FMS impact questionnaire (p=0.001, r=0.621) and negatively with the MET scale (p=0.009, r= -0.287). Patients with FMS experience greater fatigue, kinesiophobia, and inactivity. As the severity of FMS worsens, so do disability, kinesiophobia, and fatigue. This study highlights the importance of breaking the cycle of fatigue and inactivity in the treatment of FMS.